Effect of material structure machining characteristics of hypereutectic al-si alloy - Moftah Saeid, Fareg Saeid (2007)
In the present research, experimental results of an investigation of dry turning of hypereutectic aluminium silicon alloy using polycrystalline diamond (PCD) tools are presented. Attention is focused on the effect of workpiece microstructure on the performance of the cutting tools in terms of tool wear, surface roughness and chip formation. The experimental study involves turning operations at three different cutting speeds: 500, 600 and 700 m/min and constant depth of cuts and feed rates. The results obtained showed that PCD tools are important in cutting this hard Al-Si alloy of reduced machinibility. The lowest cutting speed provides good machinibility and surface finish. The change of workpiece structure was induced by modifying the primary Si phase in Al-Si alloy with strontium (Sr). This attempt found that Sr alone does not lead to a significant reduction in the size of primary Si phase. However, the results indicated that if the structure is modified the tool wear improves compared to the unmodified alloy.